2022
DOI: 10.55529/jsrth.25.31.34
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Social Media Marketing of Select Beach Resorts in Pantukan

Abstract: This study sought to assess the effectiveness of social media marketing on selected beach resorts in Pantukan. The study is quantitative by nature and involved 485 Facebook users who follow the Facebook pages of beach resorts in Pantukan. A questionnaire was designed to measure the effectiveness of social media marketing. The said instrument was intentionally designed to suit the context of the study. The identified indicators of effectiveness are as follows: information, entertainment, convenience, self-expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…A study suggested that the appropriate sample size for quantitative studies will range from 30 to 500 respondents [7]. This was observed in existing studies that were quantitative by nature [8][9][10]. The respondents of this study were three hundred eighty-seven (387) restaurant employees from ten (10) selected restaurants in Tagum City.…”
Section: Methodsmentioning
confidence: 99%
“…A study suggested that the appropriate sample size for quantitative studies will range from 30 to 500 respondents [7]. This was observed in existing studies that were quantitative by nature [8][9][10]. The respondents of this study were three hundred eighty-seven (387) restaurant employees from ten (10) selected restaurants in Tagum City.…”
Section: Methodsmentioning
confidence: 99%